Analysis of learning innovation in madrasah ibtidaiyah (A diffusion study) - Asep Ediana Latip (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2022)
This study describes the diffusion process of thematic learning innovation in elementary schools. The research approach used is quantitative with diffusion research methods. Data collection techniques used are questionnaires. The data analysis used is a descriptive analysis technique. The subject of this research is elementary teachers in South Tangerang, Indonesia, which consists of elements from the Head of the Ibtidaiyah Madrasah, the Deputy Head of the Ibtidaiyah Madrasah, the Curriculum Section, Class Teachers and Subject Teachers.  Among them some teach teach at State and Private Madrasah. The results showed a diffusion process of thematic learning innovations in Madrasah Ibtidaiyah from 2013-2019. This process is proven by 85% who perceive the attributes of thematic learning innovations as relatively positive innovations, so they are positively related to the rate of adoption of thematic learning innovations. Furthermore, various types of communication in the thematic learning innovation-decision process at Madrasah Ibtidaiyah. These findings recommend the application of thematic learning innovations at Madrasah Ibtidaiyah, South Tangerang, and optimizing the development of its implementation through various activities involving the synergy of practitioners, academics, and madrasah services.